Characterization of the Immune Status of CD8(+) T Cells in Oral Lesions of Human Immunodeficiency Virus-Infected Persons with Oropharyngeal Candidiasis - Leigh, Janet E. (American Society for Microbiology, 2006)
Oropharyngeal candidiasis (OPC) remains the most common oral infection in human immunodeficiency virus (HIV) disease. In a high percentage of HIV(+) persons with reduced CD4(+) T cells, oral lesions with Candida present at the outer epithelium have an accumulation of CD8(+) T cells at the epithelium-lamina propria interface associated with reduced expression of the mucosal cell-trafficking adhesion molecule E-cadherin. The purpose of the present study was to characterize the immune status of these CD8(+) T cells. Immunohistochemical staining for phenotypic and activation and costimulation markers was performed on frozen biopsy tissue sections from HIV(+) OPC(+) persons with accumulated CD8(+) T cells. CD8(+) T cells consisted primarily of central memory cells by virtue of positive CD45RO (memory) and CD27 (central memory) expression. However, concomitant negative expression of CD62L and CCR7 (effector memory) was suggestive of a transitioning memory phenotype within the tissue. Despite this, the cells are considered to be activated on the basis of positive expression of CD69. The CD8(+) T cells are not considered to be NK T cells or anti-HIV CD8(+) T cells because of negative or low expression of CD161 and vascular cell adhesion molecule, respectively. These results suggest that the accumulated mucosal migratory-challenged CD8(+) T cells are otherwise normal memory T cells in an activated state.